Quality of care in an intensive care unit for the prevention of pressure injuries - de Oliveira Rebouças, Ruhama; de Brito Belchior, Amelina; Dean Barbosa Marques, Antonio; Vieira Figueiredo, Sarah; Fontenele Lima de Carvalho, Rhanna Emanuela; Karanini Paz de Oliveira, Sherida (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to identify safe practices for the prevention of pressure injury (PI), performed by nurses in an intensive care unit (ICU) and to classify the quality of care. Method: cross-sectional study conducted with 11 nurses in an ICU of a hospital in Fortaleza - Ceará, using a pressure injury prevention questionnaire adapted for pediatrics, in October and November 2018. Descriptive statistics and the Positivity Index (PIx) of the quality of care were used. Results: there was a poor assistance, according to the PIx, in the three domains: preventive measures and early detection of LP (PIx: 66.6% + 24.5); pressure relief measures (PIx: 41.9% + 21.6) and assessment and notification (PIx: 65.1% + 14.5), with a general average PIx equal to 57.8% (Standard Deviation: +13 , 8), and preventive actions carried out inappropriately. Conclusion: it was possible to identify scarce good practices, which implies poor and insecure assistance. It is urgent to plan and implement improvement strategies with a view to patient safety and quality of care.